COMPARATIVE DYNAMICS OF THE MAIN TRENDS OF DEVELOPMENT ECONOMIES OF THE RUSSIAN FEDERATION AND ITS INDUSTRIAL SECTOR - Svetlana Galazova (Вестник Северо-Кавказского федерального университета)
In article the features of dynamics of economy of the Russian Federation and its industrial sector reflecting various periods of their development (ascending are considered, the compensatory and descending dynamics) that allowed to determine resultant parameters of the state industrial policy and to prove efficiency of the anti-recessionary tools directed on preservation industrial and the technological making economy of Russia.